2016
DOI: 10.1093/dnares/dsw012
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of the draft genome of buckwheat and its applications in identifying agronomically useful genes

Abstract: Buckwheat (Fagopyrum esculentum Moench; 2n = 2x = 16) is a nutritionally dense annual crop widely grown in temperate zones. To accelerate molecular breeding programmes of this important crop, we generated a draft assembly of the buckwheat genome using short reads obtained by next-generation sequencing (NGS), and constructed the Buckwheat Genome DataBase. After assembling short reads, we determined 387,594 scaffolds as the draft genome sequence (FES_r1.0). The total length of FES_r1.0 was 1,177,687,305 bp, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
147
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(149 citation statements)
references
References 74 publications
2
147
0
Order By: Relevance
“…As the first step of our quinoa genome project, we estimated the genome size using the frequency distribution curve of 17-mer obtained from Illumina short reads, as successfully reported in previous studies 35 , 65 . The k-mer frequency distribution curve (k-mer =17) using paired-ends (PEs) with a 185-bp insert size is shown in Supplementary Figure S1.…”
Section: Resultsmentioning
confidence: 99%
“…As the first step of our quinoa genome project, we estimated the genome size using the frequency distribution curve of 17-mer obtained from Illumina short reads, as successfully reported in previous studies 35 , 65 . The k-mer frequency distribution curve (k-mer =17) using paired-ends (PEs) with a 185-bp insert size is shown in Supplementary Figure S1.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we consider that by fixing the photoperiod sensitivity genes, it is thought that ecotype breeding could be carried out more efficiently even in allogamous buckwheat. In recent years, data required for molecular breeding of common buckwheat, such as the draft genome (Yasui et al 2016), buckwheat genome database (http://buckwheat.kazusa.or.jp), and a high-density linkage map (Yabe et al 2014), have been used to increase the yielding ability by genomic selection (Yabe et al 2018). and several previous studies.…”
Section: Ecotype and Ecological Differentiationmentioning
confidence: 99%
“…be a transcription factor, has been identified as a candidate gene for the I s or G gene; it is expressed only in the style of thrum plants and is linked to the S locus with no recombination in buckwheat (Yasui et al 2012). Using genome assembly analysis with next-generation sequencing (NGS), we have developed a buckwheat genome database (BGDB) and also found that the region that includes this locus is absent in the genome of pin plants (Yasui et al 2016). The S h alleles have a deletion of a nucleotide in the S-ELF3 locus, which causes a frame shift.…”
Section: Introductionmentioning
confidence: 99%
“…Because the region of the S-ELF3 locus is missing in the genome of s plants (Yasui et al 2016), we needed to detect the flanking regions of the S h alleles that would be present in the s genome. In this study, we used NGS analysis in combination with bulked segregant analysis of segregating progeny of a cross between SI and SC plants.…”
Section: Introductionmentioning
confidence: 99%